Gecikmiş veda: Bir Olgu Sunumu - (:unkn) unknown (My University, 2012)
Kayıp insan yaşamının kaçınılmaz bir parçasıdır ve yas sürecini ortaya çıkarmaktadır. Yas süreci çözümlenemediğinde, yas sonrası beklenen yaşama yeniden uyum zorlaşabilmektedir. Bu olguda çoğul kayıpları olan bir kadın danışanla sürdürülen danışmanlık sürecini, gecikmiş yas tepkileri bağlamında tartışmak ve süreci bu alanda çalışan sağlık profesyonelleri ile paylaşmak amaçlanmıştır.

Losing someone is an unavoidable part of human life and results in a pro- cess of mourning. When the mourning process cannot be resolved, the ex- pected readaptation to life after such a loss can be difficult. In this report, a female patient who experienced multiple losses and demonstrated delayed mourning is discussed for the purpose of sharing her ongoing counselling process with health professionals working in this field.
The DelayedGoodbye:A Case Presentation
Keywords: Hemşirelik